2003
DOI: 10.1002/uog.770
|View full text |Cite
|
Sign up to set email alerts
|

P303: Prenatal diagnosis of foramen ovale obstruction?a report of two cases

Abstract: th World Congress on Ultrasound in Obstetrics and GynecologyPoster abstracts outlet right ventricle, premature closure of the foramen ovale and a levoatrial cardinal vein draining into the innominate vein. In a prior study performed elsewhere the levoatrial cardinal vein had been interpreted as an aortic arch perfused retrogradely, and hypoplastic left heart syndrome had been diagnosed. Prenatal management, induction at 38 weeks and postnatal studies and treatment are presented. To the best of our knowledge, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(25 citation statements)
references
References 21 publications
1
24
0
Order By: Relevance
“…In these cases, the prognosis for the fetuses is poor . However, the studies on premature rFO/cFO in fetuses with otherwise structurally normal hearts are anecdotal case reports or small series with variable neonatal outcomes …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In these cases, the prognosis for the fetuses is poor . However, the studies on premature rFO/cFO in fetuses with otherwise structurally normal hearts are anecdotal case reports or small series with variable neonatal outcomes …”
Section: Introductionmentioning
confidence: 99%
“…otherwise structurally normal hearts are anecdotal case reports or small series with variable neonatal outcomes. [6][7][8] The aims of this study were to characterize the fetal echocardiographic features of rFO/cFO in otherwise structurally normal fetal hearts, to evaluate the outcome, and to identify risk factors for adverse outcome in a large cohort from a regional and national referral fetal imaging center.…”
mentioning
confidence: 99%
“…In normal fetuses, 40% of the systemic venous blood crosses the foramen ovale to the left ventricle, while in patients with tricuspid atresia, the entire systemic venous blood will cross through the atrial septum . While flow restriction at the atrial septal level rarely causes heart failure in fetuses with structurally normal hearts, it can cause important fetal distress and decreased cardiac output in fetuses with tricuspid atresia . This could alter fetal hemodynamics and may result in sub‐optimal fetal growth.…”
Section: Discussionmentioning
confidence: 99%
“…Phillipos et al have followed the FO in fetuses between 20 and 38 weeks of gestation and reported that the increase in the diameter of FO is directly proportional to the number of gestational weeks [25]. According to some studies, fetuses with subnormal FO diameters may experience altered fetal hemodynamics (blood flow in umbilical vein, DV and vena cava inferior) leading to hemodynamic disorders ranging from mild right-sided cardiac failure to severe hydrops fetalis [26][27][28]. On the other hand, increased FO diameter has been associated with atrial septal defect (ASD) in postnatal life.…”
Section: Discussionmentioning
confidence: 99%